The Effect of a Competency-Based Learning Approach on Improving English Speaking Skills: Survey Study in Higher Education - Nanda Pambudi; Hariadi Syam; Utary Rustam; Ratna Ayu Pawestri Kusuma Dewi; Hasbiyah Srianah Amir (Yayasan Adra Karima Hubbi, 2024)
Background. During ongoing learning, many students are found who do not master how to speak English properly and correctly. This can be seen when they communicate. For this reason, improving the ability to speak English in higher education is very important in facing the challenges of globalization and increasing workforce needs. A competency-based learning approach is a solution that is used as an effective method to achieve improvements in speaking abilities. Purpose. The aim of this research is to find out whether implementing a competency-based learning approach can improve students' ability to speak English. Method. This research method uses quantitative research methods with a survey approach. The survey used in this research was seen from student participants at several universities that implement a competency-based learning approach in learning English. Data was collected through questionnaires given to students who assessed the learning approach and their English speaking skills before and after implementing the learning approach. Results. The results of this research state that universities that implement a competency-based learning approach provide a positive impact and great opportunities for students in higher education to improve their English speaking skills. The survey results also show that students are satisfied with competency-based learning. Conclusion. The conclusion of this research explains that the competency-based learning approach is effective in improving English speaking skills in higher education. The implication of this research is the importance of implementing a learning approach that is appropriate to current global needs to prepare students with relevant and competent skills in English.